Staphylococcus aureus drives expansion of low-density neutrophils in diabetic mice - Cohen, Taylor S.; Takahashi, Virginia; Bonnell, Jessica; Tovchigrechko, Andrey; Chaerkady, Raghothama; Yu, Wen; Jones-Nelson, Omari; Lee, Young; Raja, Rajiv; Hess, Sonja; Stover, C. Kendall; Worthington, John J.; et al. (The Journal of Clinical Investigation, 2019)
Diabetic individuals are at considerable risk for invasive infection by Staphylococcus aureus, however, the mechanisms underlying this enhanced susceptibility to infection are unclear. We observed increased mortality following i.v. S. aureus infection in diabetic mice compared with nondiabetic controls, correlating with increased numbers of low-density neutrophils (LDNs) and neutrophil extracellular traps (NETs). LDNs have been implicated in the inflammatory pathology of diseases such as lupus, given their release of large amounts of NETs. Our goal was to describe what drives LDN increases during S. aureus infection in the diabetic host and mechanisms that promote increased NET production by LDNs. LDN development is dependent on TGF-β, which we found to be more activated in the diabetic host. Neutralization of TGF-β, or the TGF-β–activating integrin αvβ8, reduced LDN numbers and improved survival during S. aureus infection. Targeting S. aureus directly with MEDI4893*, an α toxin–neutralizing monoclonal antibody, blocked TGF-β activation, reduced LDNs and NETs, and significantly improved survival. A comparison of gene and protein expression in high-density neutrophils and LDNs identified increased GPCRs and elevated phosphatase and tensin homolog (PTEN) in the LDN subset. Inhibition of PTEN improved the survival of infected diabetic mice. Our data identify a population of neutrophils in infected diabetic mice that correlated with decreased survival and increased NET production and describe 3 therapeutic targets, a bacterial target and 2 host proteins, that prevented NET production and improved survival.